2021
DOI: 10.1002/alz.12369
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale plasma proteomic profiling identifies a high‐performance biomarker panel for Alzheimer's disease screening and staging

Abstract: Introduction Blood proteins are emerging as candidate biomarkers for Alzheimer's disease (AD). We systematically profiled the plasma proteome to identify novel AD blood biomarkers and develop a high‐performance, blood‐based test for AD. Methods We quantified 1160 plasma proteins in a Hong Kong Chinese cohort by high‐throughput proximity extension assay and validated the results in an independent cohort. In subgroup analyses, plasma biomarkers for amyloid, tau, phosphorylated tau, and neurodegeneration were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(100 citation statements)
references
References 73 publications
8
84
0
Order By: Relevance
“…In our study, OSM and MMP9 were 2 of the 116 proteins that showed non-zero contributions to variation from diagnosis by VCA. A smaller cohort of Hong Kong Chinese ( n = 180) found 429 differentially abundant proteins in AD plasma (out of 1,160 tested), which included AXIN1 and uPA ( 16 ). In a large study of protein quantitative trait loci and Olink quantified serum proteomes in 2,893 individuals, CD33 protein was causally linked to AD disease traits ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, OSM and MMP9 were 2 of the 116 proteins that showed non-zero contributions to variation from diagnosis by VCA. A smaller cohort of Hong Kong Chinese ( n = 180) found 429 differentially abundant proteins in AD plasma (out of 1,160 tested), which included AXIN1 and uPA ( 16 ). In a large study of protein quantitative trait loci and Olink quantified serum proteomes in 2,893 individuals, CD33 protein was causally linked to AD disease traits ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although other studies suggest that the APOE genotype can improve the performance of AD classifiers as an additional feature [ 43 , 44 ], no significant improvement was observed in this study ( Supplementary Table S4 ), which may be due to the fact that the APOE level is already present in all of these classifiers as one of the two most important features ( Figure 3 B). On the other hand, the 19-protein biomarker panel generated in a recent large-scale study of an Asian cohort also did not include APOE but was nevertheless able to distinguish patients with AD irrespective of their APOE genotype [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the eight new potential markers revealed in this study, C1QB, A2AP, CAMP and APOC4 should be especially noted, as their p -values were <0.05. In addition, changes in the plasma levels of TENA, PAI1 and VCAM1 have been recently shown to be associated with AD in a large-scale Asian cohort using proximity extension assay technology for the quantification of 1160 plasma proteins [ 37 ]. It is also noteworthy that the upregulation of VCAM1 and downregulation of PAI observed in the current study agree with other results reported in the literature [ 26 , 37 ], and the downregulation trend of PAI1 was also shown for MCI [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, tests of the genes associated with AD, including APP , BACE1 , PSEN1 , APOE (apolipoprotein E) ε4 alleles, and TREM2 , and calculation of the polygenic risk score should be performed [ 154 ]. Proteomic profiling is an alternative biomarker panel for AD, the results of which can offer directions for further exploration of new biomarkers [ 82 , 155 , 156 ]. Last, biomarkers should be central to the model, including the central framework (PET, CSF assays, or biopsy) and the peripheral framework (plasma or other biofluid assays).…”
Section: Complete Model Based On the Biomarkers Of Admentioning
confidence: 99%